SURVEI PELAKSANAAN KEGIATAN EKSTRAKURIKULER OLAHRAGA PADA SEKOLAH DASAR NEGERI DI KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR TAHUN 2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study is the researchers wanted to know about: 1 Process sports extracurricular activities at public elementary school in the District Ngargoyoso Karanganyar Year 2013 population used in this study were all public elementary school in the District Ngargoyoso Karanganyar totaling 22 Elementary School . Techniques of data collection using questionnaire, interview, observation and documentation. Results of field observations we can see that the obstacles that occur in the field are highly constrained infrastructure and also funding only comes to the allocation of BOS funds. Dipeorleh research results showed that the implementation of extracurricular sports at public elementary school in the District Ngargoyoso Karanganyar In 2013 included in both categories.